Screening blood glucose and blood pressure to prevent the risk of diabetes mellitus and hypertension - Yoni Astuti; Agus Suharto; Rifki Hulalata (Universitas Ahmad Dahlan, 2022)
During the covid 19 pandemic, Gamping Lor did not hold activities that risk causing crowds in order to avoid the transmission of covid 19, thus they didn’t do any activity. This condition will worsen public health conditions, which are vulnerable to exposure to NCD (Non-Communicable Diseases). In Indonesia, the number of people with DM (Diabetes mellitus) is estimated to increase by 2 times in 2030. The purpose of this service is to conduct screening for early detection of diabetes and hypertension in vulnerable communities of Gamping Lor. The method used is counseling and examination practice. The results of the activity there were 68 participants consisting of women 89.7% men 11.3%. with a picture of the following conditions; Hypertension, 35.3% prehypertension 27.3%, Normal 29.4%, Low 7.3%; hyperglycemia 15.2%, hypoglycemia, 4.5%, normal 83.3%; BMI status; Thin 11.11%, ideal,22.22%, Overweight, 20.6% Obesity level 1 , 34.9%; obesity grade 2; 11.11%. Participants with high hypertension conditions, but more normal sugar levels. Participants overweight to obesity are higher than the ideal and thin. Conclusion : Service I I went well according to plan. More participants were affected by pre and hypertension, but normoglucose, on the other hand, experienced the most overweight and obesity. So it is important to do a diet and fat burning program according to age.